Right hemispheric dominance in processing of unconscious negative emotion. - Sato W; Aoki S (Brain & Cognition, 2006)
Right hemispheric dominance in unconscious emotional processing has been suggested, but remains controversial. This issue was investigated using the subliminal affective priming paradigm combined with unilateral visual presentation in 40 normal subjects. In either left or right visual fields, angry facial expressions, happy facial expressions, or plain gray images were briefly presented as negative, positive, and control primes, followed by a mosaic mask. Then nonsense target ideographs were presented, and the subjects evaluated their partiality toward the targets. When the stimuli were presented in the left, but not the right, visual fields, the negative primes reduced the subjects' liking for the targets, relative to the case of the positive or control primes. These results provided behavioral evidence supporting the hypothesis that the right hemisphere is dominant for unconscious negative emotional processing.